The Use of Project Based Learning to Improve Students’ Reading Ability for Second-Year Students at MTsN 1 Kota Bengkulu - Febriani, Hanura (Yayasan Sembilan Pemuda Indonesia, 2023)
This study investigates the impact of Project-Based Learning (PBL) on the reading abilities and motivation of second-year students at MTsN 1 Kota Bengkulu Utilizing a classroom action research approach, the research was conducted over two cycles, each comprising planning, action, observation, and reflection phases. The results indicate a significant improvement in both student reading performance and motivation. In Cycle I, the majority of students (42.4%) achieved a ‘Good’ performance level, while a considerable number (30.3%) fell into the ‘Low’ category, and 18.2% failed. Observations highlighted moderate engagement and participation, with students showing limited enthusiasm for reading tasks. Cycle II demonstrated marked improvements, with 46.7% of students achieving ‘Good’ performance and a significant increase in those reaching ‘Very Good’ (26.7%) and ‘Excellent’ (10%) levels. Notably, the ‘Failed’ category was eliminated. Observations revealed heightened engagement, active participation, and increased motivation, attributed to the interactive and real-world relevant nature of PBL. The role of the teacher as a facilitator was crucial in maintaining high levels of student motivation and engagement. The findings suggest that PBL is an effective instructional strategy for enhancing reading skills and motivation. Continued implementation of PBL, combined with ongoing teacher training and diverse project offerings, is recommended to sustain and further improve student outcomes.